Development of Virtual Reality Learning Media Assisted by Millealab for Islamic History Education in Secondary School - Pandu Hyangsewu; Muhamad Ridwan Sudaryat; Achmad Faqihuddin; Aulia Tegar Wicaksono; Rosmalizawati Ab Rashid (Jurusan Teknik Informatika dan Komputer, 2026)
Purpose – This study aims to develop and test the feasibility and practicality of a virtual tour learning media assisted by the Millealab platform for Islamic history material on the Ottoman Empire at one of the SMP in Bandung. Design/methods/approach – This study uses a Research and Development (R&D) design through the procedural ADDIE model approach (Analysis, Design, Development, Implementation, and Evaluation). Sampling was conducted using a random sampling technique involving 167 students for needs analysis and 30 students for field implementation. Data collection instruments included expert validation sheets and practicality assessment questionnaires. Findings – The results showed that the virtual tour product achieved